2003
DOI: 10.1002/ijc.11297
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils influence melanoma adhesion and migration under flow conditions

Abstract: We have studied human melanoma cell (C8161) adhesion and migration in response to stimulation by soluble collagen IV (CIV) using a modified Boyden chamber. In this modified chamber, shear flow can be introduced over the cell-substrate interface, affecting tumor cell chemotactic migration through a microporous filter. A relatively high level of intercellular adhesion molecule-1 (ICAM-1) was found on C8161 cells. In contrast, levels of ␤ 2 -integrins (e.g., LFA-1 and Mac-1), the molecules that would be necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 34 publications
4
100
0
5
Order By: Relevance
“…54 It has been shown in vitro that stationary neutrophils can facilitate tumor cell arrest and transmigration across endothelial monolayers via binding interactions between adherent neutrophils and passing tumor cells that are both adhesion molecule-and shear rate-dependent. 30,31,55,56 In vivo, we found that systemic inflammation increased tumor cell recruitment in the liver sinusoids when leukocytes simultaneously adhered in these vessels. Indeed, almost 80% of tumor cells were colocalized with adherent neutrophils in the sinusoids of LPS inflamed mice.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…54 It has been shown in vitro that stationary neutrophils can facilitate tumor cell arrest and transmigration across endothelial monolayers via binding interactions between adherent neutrophils and passing tumor cells that are both adhesion molecule-and shear rate-dependent. 30,31,55,56 In vivo, we found that systemic inflammation increased tumor cell recruitment in the liver sinusoids when leukocytes simultaneously adhered in these vessels. Indeed, almost 80% of tumor cells were colocalized with adherent neutrophils in the sinusoids of LPS inflamed mice.…”
Section: Discussionmentioning
confidence: 83%
“…We asked whether sequestration of neutrophils, within the liver microvasculature contributed to the observed increase in tumor cell arrest in systemically inflamed animals, as has been suggested by the in vitro work of others. 30,31 First, the kinetics of LPS-induced leukocyte recruitment within the hepatic vasculature was measured by intravital microscopy as others and we previously described. 40,42,43 Leukocyte adhesion in sinusoids and postsinusoidal venules increased by 8-and 17.5-fold, respectively, relative to untreated controls (Figs.…”
Section: Leukocyte-tumor Cell Interactions Contribute To the Increasementioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, L-selectin on monocytes acting synergistically with P-selectin on platelets has been implicated in promoting colon cancer metastasis (14). It has also been shown that L-selectin expressed on human neutrophils is necessary to bind LS174T cells (15), but this molecule is apparently not involved in the neutrophil-mediated recruitment of melanoma cells (lacking L-selectin ligands) to stimulated endothelium (27).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils activated by melanoma-secreted IL-8 can facilitate melanoma cell extravasation through an interaction between ICAM-1 (CD54) on the melanoma cells and Mac-1 (CD11b/CD18) on neutrophils [253,254,293]. Neutrophils were also shown to be important for entrapping circulating melanoma cells and thus facilitating lung metastasis development [294].…”
Section: Promotion Of Cancer Cell Dissemination By Neutrophilsmentioning
confidence: 99%